Identification and simultaneous quantification of five alkaloids in Piper longum L. by HPLC–ESI-MSn and UFLC–ESI-MS/MS and their application to Piper nigrum L. (15th June 2015) - Liu, Hao-Long; Luo, Rong; Chen, Xiao-Qing; Ba, Yin-Ying; Zheng, Li; Guo, Wei-Wei; Wu, Xia
Highlights: Five alkaloids were isolated and identified from P. longum L. by HPLC–ESI-MS n . Total alkaloids of P. longum L. (PLA) were purified and prepared. A UFLC–ESI-MS/MS method was developed to simultaneously quantify five alkaloids. The contents of five alkaloids were different between PLA and material of P. longum and P. nigrum . Abstract: A simple, effective and suitable UFLC–ESI-MS/MS method was firstly developed to simultaneously determine five characteristic constituents (piperine, piperlonguminine, Δα, β-dihydropiperlonguminine, pellitorine and piperanine) of Piper longum L. The total alkaloids of P. longum L. was prepared. The alkaloid contents of Piper nigrum L. and P. longum L. were compared. The analysis was carried out in multiple reaction monitoring scan mode. The method showed a good specificity, linearity ( R 2 > 0.995), stability (RSD < 2.53%), repeatability (RSD < 2.58%), and recovery (90.0–103.5%). The limits of detection and limits of quantification of five alkaloids were in the range of 0.02–0.03 and 0.05–0.10 ng/mL, respectively. The intra- and inter-day precision was less than 9.30% and 9.55%, respectively. The validation results confirmed that the method could simultaneously determine the target alkaloids in the sample. Furthermore, the identities of the alkaloids were verified by HPLC–ESI-MS/MS. Compared with P. nigrum, P. longum had lower piperine content but was enriched in the other four alkaloids.